2023
DOI: 10.1002/mp.16450
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy of the biodistribution and internal radiation dosimetry of 13N‐ammonia using a total‐body PET/CT scanner

Abstract: BackgroundConventional short‐axis PET typically utilizes multi‐bed multi‐pass acquisition to produce quantitative whole‐body dynamic images and cannot record all the uptake information simultaneously, resulting in errors when fitting the time‐activity curves (TACs) and calculating radiation doses.PurposeThe aim of this study is to evaluate the 13N‐ammonia biodistribution and the internal radiation doses using a 194 cm long total‐body PET/CT scanner (uEXPLORER), and make a comparison with the previous short‐axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Currently, most research in TB-PET data processing is focused on 18 F-FDG imaging, and the potential for non-FDG tracers must be leveraged. Some pioneering works have attempted imaging with 68 Ga-DOTATATE [116], 68 Ga-PSMA [117], 68 Ga-FAPI [118][119][120], 13 N-ammonia [121], 89 Zr [122,123], 18 F-Fluciclovine [124], 11 Cmethionine [125], Y-90 [126], and 82 Rb [127]. However, the optimal data processing methods differ considerably between non-FDG tracers, and need to be adapted accordingly.…”
Section: Future Directionsmentioning
confidence: 99%
“…Currently, most research in TB-PET data processing is focused on 18 F-FDG imaging, and the potential for non-FDG tracers must be leveraged. Some pioneering works have attempted imaging with 68 Ga-DOTATATE [116], 68 Ga-PSMA [117], 68 Ga-FAPI [118][119][120], 13 N-ammonia [121], 89 Zr [122,123], 18 F-Fluciclovine [124], 11 Cmethionine [125], Y-90 [126], and 82 Rb [127]. However, the optimal data processing methods differ considerably between non-FDG tracers, and need to be adapted accordingly.…”
Section: Future Directionsmentioning
confidence: 99%
“…Owing to its ultra-high sensitivity, TB-PET has emerged as a prominent research tool for enhancing the accuracy of internal radiation dose calculations in clinical applications [24,25]. Yu et al [24] demonstrated that TB-PET is capable of simultaneously measuring the time-course activity of 13 N-ammonia in all organs of the body. This capability offers more precise biodistribution data and radiation dose estimations compared with SAFOV PET.…”
Section: Improved Accuracy Of Radiation Dosimetrymentioning
confidence: 99%
“…Yu et al. [24] demonstrated that TB‐PET is capable of simultaneously measuring the time‐course activity of 13 N‐ammonia in all organs of the body. This capability offers more precise biodistribution data and radiation dose estimations compared with SAFOV PET.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation